RUNX1/RUNX1T1 mediates alternative splicing and reorganises the transcriptional landscape in leukemia - Vasily V. Grinev; Farnaz Barneh; Ilya M. Ilyushonak; Sirintra Nakjang; Job Smink; Anita van Oort; Richard Clough; Michael Seyani; Hesta McNeill; Mojgan Reza; Natalia Martinez-Soria; Salam A. Assi; et al. (Nature Communications, 2021)
The fusion gene RUNX1/RUNX1T1 is oncogenic in acute myeloid leukemia. Here, the authors show that the fusion gene alters the transcriptional landscape of the cells by changing the structure of the 5’UTR, altering isoform expression, and controlling the expression of splicing factors.